Managing capital flows: The case of Singapore - Hwee Kwan Chow (Asian Development Bank Institute (ADBI), 2008)
The resurgence of private capital inflows into Asia in recent years has raised the question of whether the region is susceptible to yet another financial crisis. While a sudden large-scale reversal of capital flows is not likely to result in a liquidity crunch or balance of payments crisis, the attendant sharp corrections in asset prices will have an adverse impact on the economy particularly through indirect channels. We present, in this study, Singapore's experience in managing the risks posed by capital flows as well as the retention of control over exchange rates and monetary conditions. It is the overall package of policies-including strong economic fundamentals and a robust financial system, prudent policy management on both the fiscal and monetary side, and credible exchange rate policy aligned with underlying fundamentals-and having the latitude to react promptly and on a sufficiently large scale to economic and financial developments that serve to increase Singapore's resilience towards disruptive swings in capital flows.
Keywords: E58; F31; G28; 330; Kapitalimport; Branchenentwicklung; Finanzsektor; Geldpolitik; Singapur